Production of clusters and thin films of nitrides, oxides and carbides by pulsed laser ablation and deposition. (2004) - Orlando, S.; Paladini, A.; Santagata, A.; Marotta, V.; Parisi, G. P.; Satta, M.; Scuderi, D.; Catone, D.; Giardini, A.; Mele, A.
Abstract : A short introduction on the principles of laser-matter interaction, material evaporation, plume formation, its reactivity with suitable gases and finally deposition are here illustrated. Experiments by mass spectrometry of formation of clusters, precursors of thin films and nanoparticles of oxides, nitrides and carbides by pulsed laser ablation (PLA) are reported. Pulsed laser ablation of targets combined with an intense atomic source produced by radiofrequency (RF), are discussed in terms of generating chemical reactions or supplying the loss of volatile components.